Study of the Naphthenic Corrosion of AISI 316 and AISI 1020 Steels by Light, Scanning Electron and Atomic Force Microscopies (LM, SEM and AFM) - Domingos,Débora V. (2018)
Corrosion processes were evaluated for AISI 316 and AISI 1020 steels by scanning electron microscopy (SEM), atomic force microscopy (AFM) and light microscopy. Coupons were immersed in four crude oil samples with different total acid numbers (TANs) for 48 days at room temperature. The steels were also exposed to three blends (B1-B3), produced by quaternary mixtures of the oils, with lower TANs than their respective original oils. SEM micrographs showed pitting-type corrosion in most cases. AFM imaging showed drastic changes in the peak-to-peak values, topographic profiles and phase images of the AISI 1020 coupons exposed to all oils and blend B3 as compared to the unexposed steel. Defects were produced on the surface of almost all the samples exposed to naphthenic corrosion. Exposure to the oil blends reduced the extent of the naphthenic corrosion on the coupons, especially blends B1 and B2. The oil mixtures (blends) reduced corrosion.